1985
DOI: 10.1002/aic.690310419
|View full text |Cite
|
Sign up to set email alerts
|

Simple, analytical criteria for the sequencing of distillation columns

Abstract: A quantitative criterion for the selection of simple distillation sequences is derived for ideal mixtures. A simple cost model, along with a shortcut solution of Underwood's equations, gives an analytical form for the total vapor rate, which is the key design variable. The results for column sequencing that are based on the analytical criterion agree well with more exact solutions, but they indicate that in numerous situations the commonly accepted heuristics are incorrect. SCOPEThe synthesis of a distillatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…For completeness, feed compositions in regions III, IV, and V requiring but one binary column, and the product regions α, β, and δ without the need for separations are indicated. The accurate results of the complete solution map for varying feeds agree with simplified heuristics proposed by Malone et al (1985). The complete solution maps computed with the novel approach can be used to decide on optimal column configurations when feed compositions are changing from day to day, as is the case in batch processes campaigns used in pharmaceutical manufacturing sites (e.g., Chakraborty and Linninger, 2002, 2003).…”
Section: Applicationssupporting
confidence: 81%
“…For completeness, feed compositions in regions III, IV, and V requiring but one binary column, and the product regions α, β, and δ without the need for separations are indicated. The accurate results of the complete solution map for varying feeds agree with simplified heuristics proposed by Malone et al (1985). The complete solution maps computed with the novel approach can be used to decide on optimal column configurations when feed compositions are changing from day to day, as is the case in batch processes campaigns used in pharmaceutical manufacturing sites (e.g., Chakraborty and Linninger, 2002, 2003).…”
Section: Applicationssupporting
confidence: 81%
“…Although the difference is only some 1.0%, the DCS shown in Figure 6a is better than the one shown in Figure 6b. This minor difference has also been confirmed in other studies (Malone et al, 1985;Gadkari and Govind, 1988). The TACs corresponding to all arrangements shown in Figure 1 are presented in Table 6 in increasing order.…”
Section: Example 1: a Typical Five-component Mixturesupporting
confidence: 79%
“…The TAC corresponding to this DCS is 3.159 × 10 6 $/year. This DCS is also reported as the optimum simple DCS by other researchers (Malone et al, 1985;Gadkari and Govind, 1988;Glinos and Malone, 1989;Porter and Momoh, 1991;Rong et al, 2001). There is also a slightly different configuration proposed by some of the researchers (Floquet et al, 1994;Jobson, 1997;Shah and Kokossis, 2001) and is shown in Figure 6b.…”
Section: Example 1: a Typical Five-component Mixturementioning
confidence: 71%
See 1 more Smart Citation
“…Another intuitive measure is based on the commonly-used six-tenth rule for equipment cost correlation: n-I Objective Function = (L,D,)o.6 (1) , = I for the separation of an n-component mixture, where L, and Dj are the separation mass load and the cost index of separation of the i-th simple separator, respectively. Malone et al (1985) proposed the total annualized cost (TAC), which is a function of the number of trays, N, and the vapor rate, V , as the basis to determine the optimal sequence. The problem of optimal separation sequence synthesis is further complicated by the introduction of justifiable options of stream splitting and blending that require little energy, but can offer considerable improvement in process economics.…”
mentioning
confidence: 99%